2014
DOI: 10.3402/tellusb.v66.22550
|View full text |Cite
|
Sign up to set email alerts
|

Insights on nitrate sources at Dome C (East Antarctic Plateau) from multi-year aerosol and snow records

Abstract: A B S T R A C THere we present the first multi-year record of nitrate in the atmospheric aerosol (2005Á2008) and surface snow (2006Á08) from central Antarctica. PM10 and size-segregated aerosol, together with superficial snow, have been collected all year-round at high resolution (daily for all the snow samples and for most of aerosol samples) at Dome C since the 2004/05 field season and analysed for main and trace ionic markers. The suitability of the sampling location in terms of possible contamination from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…(3), the net adsorption rate is expressed as Ullerstam et al (2005b) have shown that for partial pressures of HNO 3 lower than 10 −5 Pa the ice surface is not entirely covered with HNO 3 and, therefore, undersaturated. The annual average atmospheric partial pressure of HNO 3 recorded at Dome C is ∼ 10 −6 Pa (Traversi et al, 2014) and is ∼ 10 −7 Pa at Halley ; hence, the ice surface is unlikely to be saturated with HNO 3 . A nonequilibrium kinetic approach is taken instead of an equilibrium adsorption as natural snowpacks are constantly undergoing sublimation and condensation of H 2 O, especially in the skin layer, due to temperature gradients present over a range of timescales from a fraction of seconds to days and seasons (Bartels-Rausch et al, 2014).…”
Section: Model 1 -Surface Adsorption or Solvation And Solid Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3), the net adsorption rate is expressed as Ullerstam et al (2005b) have shown that for partial pressures of HNO 3 lower than 10 −5 Pa the ice surface is not entirely covered with HNO 3 and, therefore, undersaturated. The annual average atmospheric partial pressure of HNO 3 recorded at Dome C is ∼ 10 −6 Pa (Traversi et al, 2014) and is ∼ 10 −7 Pa at Halley ; hence, the ice surface is unlikely to be saturated with HNO 3 . A nonequilibrium kinetic approach is taken instead of an equilibrium adsorption as natural snowpacks are constantly undergoing sublimation and condensation of H 2 O, especially in the skin layer, due to temperature gradients present over a range of timescales from a fraction of seconds to days and seasons (Bartels-Rausch et al, 2014).…”
Section: Model 1 -Surface Adsorption or Solvation And Solid Diffusionmentioning
confidence: 99%
“…In particular, concentrations of sea salt and other particles that may scavenge atmospheric HNO 3 are low on the East Antarctic Plateau (Legrand et al, 2016). Hence, the main atmospheric nitrate is gaseous HNO 3 that dissolves in or adsorbs onto snow grains (Traversi et al, 2014).…”
Section: Model Validationmentioning
confidence: 99%
“…Stratospheric inputs of nitrate are believed to be mostly caused by the sedimentation of polar stratospheric clouds (PSCs) in winter (Seinfeld and Pandis, 1998;Jacob, 1999). The interpretation of nitrate deep ice-core records remains elusive (e.g., Wolff et al, 2010), mainly because its deposition to the snow is not irreversible (Traversi et al, 2014, and references therein) at low-accumulation sites such as Dome C or Vostok (78…”
Section: Introductionmentioning
confidence: 99%
“…However, there are many uncertainties and speculations over the sources of nitrate, its seasonality, and post-depositional losses (e.g. Traversi et al, 2014;Shi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on its origin (e.g. Wolff, 1995;Wagenbach et al, 1998;Traversi et al, 2014), seasonal and spatial variations (e.g. Dahe et al, 1992;Lee et al, 2014;Savarino et al, 2007), air-snow interactions (e.g.…”
Section: Introductionmentioning
confidence: 99%